Zn-doped CuO nanocomposites inhibit tumor growth by NF-κB pathway cross-linked autophagy and apoptosis. (5th November 2018) - Xu, Huanli; Yuan, Ru; Liu, Xiaohui; Li, Xiao; Qiao, Gan; Li, Cong; Gedanken, Aharon; Lin, Xiukun
Aim: To investigate the antitumor effects and action mechanism of Zn-doped CuO nanocomposites (Zn-CuONPs).Materials & methods: Therapeutic effects and mechanisms of Zn-CuONPs were investigated both in vitro and in vivo .Results: Zn-CuONPs could inhibit tumor growth both in vitro and in vivo significantly. Zn-CuONPs treatment resulted in cytotoxicity, reactive oxygen species (ROS) production, DNA damage, apoptosis and autophagy. ROS scavenger N -acetylcysteine attenuated all of the above effects induced by Zn-CuONPs. N -acetylcysteine also restored the effects of Zn-CuONPs on protein expressions related to apoptosis, autophagy and NF-κB pathways. NF-κB pathway inhibitor pyrrolidine dithiocarbamate significantly attenuated Zn-CuONPs induced apoptosis and autophagy.Conclusion: Our data demonstrated that Zn-CuONPs could inhibit tumor growth both in vitro and in vivo by ROS-dependent apoptosis and autophagy cross-linked by NF-κB pathways. Graphical abstract: